Pengaruh Budaya Organisasi, Pengembangan Karir, dan Komitmen Organisasi terhadap Kinerja Karyawan Hotel Desa Wisata TMII Jakarta - Federic Mario Bolung; Endri Sentosa; Marnis Marnis (Oikonomia: Jurnal Manajemen, 2021)
Purpose The purpose of this study was to determine the effect of organizational culture, career development, and organizational commitment on the performance of hotel employees at the tourist village of TMII Jakarta. Methodology The data collection method used was a questionnaire. The number of samples used as many as 95 respondents who are employees of the Hotel Desa Wisata TMII Jakarta. Analysis technique with multiple regression. Findings The three variables of organizational culture, career development and organizational commitment either partially or jointly proved to have an effect on performance. Suggestion Companies need to pay attention to employee career development because this has proven to be the most significant.